ОСОБЛИВОСТІ КЛАСИФІКАЦІЇ АДМІНІСТРАТИВНИХ ПРОСТУПКІВ (ДЕЛІКТІВ) - Панасюк, Оксана Володимирівна (SUPREMANCE OF LAW, 2019)
Types of administrative offenses are established and characterized, criteria for classification of administrative offenses are defined and analyzed. The legal characteristics of individual classification groups of administrative offenses are given.
Keywords: administrative misconduct; classification; subjective side; objective side